Spray-dried porcine plasma added to diets contaminated with aflatoxins and fumonisins shows beneficial effects to piglet health - MÜLLER,LUCIELI K.F. (2018)
Abstract This study was aimed to analyze the effects of spray-dried porcine plasma (SDPP) on the health of post weaning piglets challenged with diets contaminated with aflatoxins and fumonisins. Fifty-six male piglets (7.15 ± 0.61 kg) were allocated in four groups: CTL group received a regular diet; SDPP group received a regular diet and 6% SDPP; MYC group received a diet containing 300 µg/kg aflatoxins and 8,000 µg/kg fumonisins; group MYC+SDPP received 300 µg/kg aflatoxins, 8,000 µg/kg fumonisins and 6% SDPP. The animals that received the experimental diet containing mycotoxins (MYC group) had lower weight gain at the end of the experiment compared to the other treatments. Animals receiving SDPP showed decreased urea levels throughout the experiment (P<0.05). Animals from MYC group presented an increased on reactive oxygen species (ROS) and thiobarbituric acid reactive substances (TBARS) levels and decreased catalase activity (P<0.05). In contrast, SDPP prevented the increase of ROS and TBARS and stimulated superoxide dismutase activity (P<0.05). In conclusion, diet contaminated with mycotoxins (group MYC) caused subclinical intoxication in the piglets, as observed by the increase on free radical’s production and lipid peroxidation. Conversely, SDPP presented a protective effect, minimizing the effects of oxidative stress caused by aflatoxins and fumonisins ingestion.